Power and place in the prehistoric Aegean and beyond: studies in honor of James C. Wright - Allen, Susan E.; Schon, Robert; Smith, R. Angus K. (INSTAP Academic Press, 2025)
"This volume celebrates the contributions and impact of our mentor, colleague, and friend, James C. Wright, on the field of Aegean Bronze archaeology in recognition of his retirement from Bryn Mawr College. The title and thematic orientation reflects his scholarly attention to power inequalities in the past, particularly as manifested through social access to architectural spaces and landscapes. The title acknowledges that Jim's interests and contributions extend beyond the domain of Aegean Prehistory, not only in terms of chronology and geography, but also in terms of his methodological approaches that have wider application. In addition to Jim's colleagues and collaborators, more than half of the contributions to the volume are by his students who collectively are but one of many signs of his profound and lasting impact not only on our scholarship, but on the discipline of archaeology itself"--
Includes bibliographical references and index
Keywords: Aegean Sea Region -- Antiquities